Intravenous Tumor Thrombus From Papillary Carcinoma of Thyroid Demonstrated by 18F-FDG PET/CT. (12th January 2022) - Wang, Yu; Jiang, Lisha; Zhang, Xinyue; Xu, Yangmengyuan; Liu, Bin
Abstract: A 24-year-old man with papillary thyroid carcinoma underwent 131 I ablation after thyroidectomy. On posttherapy whole-body scintigraphy, only the remnant thyroid was visualized. In view of elevated unstimulated thyroglobulin level 7 months after 131 I ablation, 18 F-FDG PET/CT scan was ordered for further evaluation. On PET/CT images, a large filling defect from the dilated left brachiocephalic vein to superior vena cava was noted corresponding with high FDG uptake. It was considered as a malignant thrombus.